Clinician’s perspective on the diagnosis of primary cutaneous B-cell lymphoma (Dermatology Reports, 2023)
Of all cutaneous lymphomas, 25% are primary cutaneous B-cell lymphomas (PCBCLs). Of these, primary cutaneous follicle center lymphoma (PCFCL), primary cutaneous marginal zone B-cell lymphoma (PCMZL), and primary cutaneous diffuse large B-cell lymphoma, leg type (PCDLBCL-LT) are the most common subtypes. For the diagnosis of PCBCLs, a biopsy combined with immunohistochemistry and histological examination is the gold standard. PCBCLs are categorized into indolent or intermediate to aggressive subtypes based on their clinical behavior in a clinically oriented approach. PCDLBCL-LT has an aggressive course that spreads to extracutaneous sites in about 45% of cases, whereas PCFCL and PCMZL are indolent diseases. As a result, instrumental staging is advised for PCDLBCL-LT but not for extracutaneous disease after a diagnosis of PCMZL or PCFCL. Lastly, dermatoscopy may offer a novel diagnostic tool to improve the clinical recognition of various PCBCL subtypes when used in conjunction with a strong clinical suspicion.